2008
DOI: 10.1074/jbc.m710252200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Residues Contributing to A2 Domain-dependent Structural Stability in Factor VIII and Factor VIIIa

Abstract: Factor VIII circulates as a heterodimer composed of heavy (A1A2B domains) and light (A3C1C2 domains) chains, whereas the contiguous A1A2 domains are separate subunits in the active cofactor, factor VIIIa. Whereas the A1 subunit maintains a stable interaction with the A3C1C2 subunit, the A2 subunit is weakly associated in factor VIIIa and its dissociation accounts for the labile activity of the cofactor. In examining the ceruloplasmin-based factor VIII A domain model, potential hydrogen bonding based upon spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 33 publications
2
49
0
Order By: Relevance
“…Thus, chemical denaturation appears to represent a more global effect on FVIII structure and a less specific effect for chain dissociation. We reported earlier that several residues at the A2-A3 interface (Tyr-1792, Tyr-1786, and Asp-666) possibly contributed to the binding energy only in the active FVIIIa form (21). Thus, interactions between the A2 domain of the heavy chain and A3C1C2 domains of the light chain may be minimal in the procofactor.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, chemical denaturation appears to represent a more global effect on FVIII structure and a less specific effect for chain dissociation. We reported earlier that several residues at the A2-A3 interface (Tyr-1792, Tyr-1786, and Asp-666) possibly contributed to the binding energy only in the active FVIIIa form (21). Thus, interactions between the A2 domain of the heavy chain and A3C1C2 domains of the light chain may be minimal in the procofactor.…”
Section: Discussionmentioning
confidence: 99%
“…This provides an explanation for the observation that K1967I is associated with hemophilia A. The same explanation has previously been proposed for other hemophilia A FVIII variants (21,22 …”
mentioning
confidence: 52%
“…It has been demonstrated that residues that control the dissociation rate of the A2-a2 domain from A1-a1/A3-C1-C2 dimer, and as such affect the stability of FVIIIa, are of critical importance for cofactor func-tion (20,21). For a number of hemophilia A variants carrying single amino acid substitutions, it has been suggested that a decreased stability of FVIIIa is the cause for the bleeding disorder (21,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Missense mutations may produce a variable phenotype, depending on the site where the mutation has occurred. Generally, mutations in the sequence coding for the A2 domain of the Factor VIII gene result in CRM -positive haemophilia with varying severity (Wakabayashi & Fay, 2008) as the A2 domain is responsible for the stability of the protein. Deletions of exons usually produces severe CRM-negative haemophilia A because of reading frame disruption except for deletion of exon 22 which results in an in-frame loss of 156 bp coding sequence (Youssouffian et al, 1987).…”
Section: Nature Of the Causative Mutationmentioning
confidence: 99%